The Mechanism of 2-Methyl Valeric Acid Inhibiting Virulence Regulator Ser/Thr Phosphatase (Stp1) in Staphylococcus aureus - Yang, Yanan; Gao, Yawen; Li, Xuenan (Letters in Drug Design & Discovery, 2024)
IntroductionIncreased resistance of Staphylococcus aureus (S. aureus) poses a significant threat to disease control in animal husbandry and human public health. Eukaryotic-like Ser / Thr phosphatase (Stp1) is an effective target for the regulation of bacterial virulence. In this study, potential Stp1 inhibitors were screened through virtual screening, and the inhibitory mechanism of these compounds was explored using molecular dynamics simulations.MethodsVirtual screening studies were performed using AutoDock vina 4.0 software. The SwissADME server predicted the properties of chemical absorption, distribution, metabolism, excretion, and toxicity (ADMET). Molecular dynamics simulation was performed using the Gromacs software package, and molecular mechanics/generalized Born surface area (MM/GBSA) was calculated using the Amber 10 package. The inhibition mechanism was verified using phosphatase, mutagenesis, and fluorescence quenching assays.ResultsThe 2-methylvaleric acid from foods was found to be a competitive inhibitor of Stp1, based on the kinetics of the enzymatic reaction and virtual screening. Molecular dynamics simulations revealed that 2-methylvaleric acid binds to the active center of Stp1 and reduces enzyme activity by competing with its substrate. Interestingly, the molecular modeling and kinetics of the enzymatic reactions were consistent. Energy decomposition indicated that Met39, Thr102, Ile164, Val167, and Thr170 played important roles in complex binding. Additionally, the SwissADME server showed that 2-methylvaleric acid possesses drug-like properties.ConclusionTherefore, 2-methylvaleric acid is a promising compound for further exploration because of its potential to reduce S. aureus virulence. These findings are conducive to additional discovery and design of new inhibitors.
Keywords: virtual screening